SISTEM REKRUTMEN DOSEN TETAP DAN TENAGA KEPENDIDIKAN DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Tilome, Apris A.; Mohi, Widya Kurniati; Mokodompit, Nur Eng; Musa, Meity Fredi (STISIPOL Mujahidin Buol, 2024)
This study aims to obtain an overview of the Recruitment System for Permanent Lecturers and Education Personnel at the Muhammadiyah University of Gorontalo. The research method uses a qualitative type with a descriptive approach. Data collection techniques are carried out through interviews, with a number of informants and observations and recording secondary data related to research problems. The results of the study used Dunnet's theory with 3 (three) indicators of the Process Variable theory, Independent variables and Dependent variables. The results of the study indicate that the recruitment system for permanent lecturers and education personnel at the Muhammadiyah University of Gorontalo is not fully in accordance with the Process Variable. While the Recruitment of Permanent Lecturers is in accordance with the Dependent variable, but the Recruitment of Education Personnel is not in accordance with the Dependent variable.